PHYTOCHEMICAL EVALUATION OF TILIACORA RACEMOSA COLEBR. USING GAS CHROMATOGRAPHY - MASS SPECTROMETRY (GC-MS) - C, Yogeshwari; P, Kumudha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective:The objective of this study is to characterize the phytoconstituents of Tiliacora racemosa Colebr. using gas chromatography mass spectrometry (GC-MS). Methods: Preliminary phytochemical and physicochemical analysis was carried out using standard procedures. GC-MS analysis of methanolic extract was carried out using Thermo GC-Trace Ultra version: 5.0, Thermo MS DSQ with a DB 35MS capillary standard non-polar column and gas chromatograph interfaced to a mass selective detector (MS DSQ II) with Xcalibur software. Results: Preliminary phytochemical screening revealed the presence of alkaloids, flavonoids, phenols, tannins, triterpenoids, steroids, proteins and amino acids, carbohydrates, saponins and coumarin. Quinones, anthraquinones, glycosides and fixed oil were absent. GC-MS analysis revealed the presence of 28 compounds of which quinic acid (retention times [RT]: 15.65) and inositol, 1-deoxy-(CAS) (RT: 19.24) was observed as abundant compounds. Conclusion: The presence of various bioactive compounds confirms the medicinal importance and it’s application for curing various diseases by traditional practitioners. However, isolation and characterization of potential bioactive compounds would lead to drug formulation.